MINIMIZATION OF NONIDEALITIES EFFECT OF CURRENTCONTROLLED THREE-PHASE INVERTERS BY USING VIRTUAL INDUCTOR - Ihsani Putri, Adinda
DC voltage ripple and dead-time are nonidealities which cannot be avoided in currentcontrolled three-phase inverter applications. Either dc voltage ripple and dead-time produce low order harmonics output that cause torque pulsation and instability. Larger inductance value is usually used to suppress nonidealities effect, however the system becomes costly, bulky and lossy. Feedforward and feedback methods have been mostly used to overcome nonidealities effect, but it requires accurate system parameters and more sensors. This research proposes virtual inductor concept that is simple and more intuitive to overcome the nonidealities. Virtual inductor block is added to the current controller so that the system behavior changes as if there is a real inductor connected to the circuit. Virtual inductor can be designed to only minimize the effects of nonidealities. Analysis of stability, sensitivity, steady-state error and transient as the effect of virtual inductor implementation are presented. It shows that the value of virtual inductance is limited by sensitivity at certain range of frequency and overshoot of the system. Simulation and experiment results are presented to verify the effectiveness of virtual inductor in minimizing the effects of dead-time and DC ripple which is shown in decrease of THD.